Prosopis - potential for arid land - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Prosopis species have proved valuable multipurpose trees for arid lands, and the International Prosopis Association is publishing a newsletter on the genus. Thickets of P. jubiflora (mesquite) can be grown along field boundaries, along roads and...